Management Strategy for Non-Performing Financing (NPF) at BMT Nusantara Sempu Sub-Branch: The Perspective of Maqasid Syariah - Ahmad Bagir Musthofa; Lely Ana Ferawati Ekaningsih (ICO EDUSHA, 2025)
This study aims to analyze risk management strategies for non-performing financing (NPF) at BMT Nusantara Capem Sempu from a maqasid syariah perspective. Employing a qualitative case study approach, data were collected through in-depth interviews and direct observation, and analyzed using SWOT analysis. The findings indicate that NPF arises from internal factors (weaknesses in feasibility analysis and post-disbursement monitoring) and external factors (economic instability among clients in the agricultural and trade sectors). Implemented strategies include preventive measures (strict feasibility analysis, prudential principles, and customer education) and curative actions (financing restructuring, persuasive collection, and collateral execution as a last resort). A key finding is that managerial decisions integrate financial, social, and religious values within the maqasid syariah framework. This integrated approach has proven effective in reducing NPF, enhancing member trust, and ensuring operational sustainability.